Income Inequality and Survival Strategies of Primary School Physical Education, Sport and Health Teachers - Totok Suhermanto; Ahmad Lani; Sakban Rosidi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
There is a problem in the inequality of physical education teachers experiencing many complaints from private physical education teachers regarding the low income they get far from expectations. Not a few of the teachers they look for side jobs in meeting their daily needs. This research is a quantitative descriptive research, which intends to find out and find information and a description of how to survive physical education teachers and this research uses interviews and data collection given to physical education teachers. The subject of this research is the participants of the National Seminar on Physical Education, Sports and Health for Milleneal Primary Schools which is held through the zoom application teleconference, the number of physical education teachers at the elementary school level who participated was 43 people. In this study using the Explanatory Sequential Mixed Methods method with data collection in the form of geogle form. For quantitative data analysis using the mean difference test and the craw association test to determine differences in the status of physical education teachers for qualitative data using the typification method and word gorization of physical education teachers based on their survival strategies. With the results of data analysis and typology categorization, it can be concluded that 1) There is income inequality between private and public employee teachers. 2) There is no relationship between employment status and their survival activities, and (3) There are four ideal types of teachers' survival strategies based on their employment status and survival strategies.